Thalli Growth, Propagule Survival, and Integrated Physiological Response to Nitrogen Stress of Ramalina calicaris var. japonica in Shennongjia Mountain (China) - Wang, Chuan-Hua; Wang, Ming; Jia, Rao-Zhen; Guo, Hua (Frontiers in Plant Science, 2018)
In this study, effects of nitrogen availability on growth, survival of Ramalina calicaris var. japonica, and whether it respond nitrogen stress in an integrated physiological way was evaluated. Thalli growth and propagule survival, thalli N and phosphorus (P) content, and activity of phosphomonoesterase (PME) of R. calicaris var. japonica were determined in a field experiment. Its differentiate adsorption in ammonia and nitrate, activity of,glutamine synthetase(GSA) and nitrate reductase (NRA) also were investigated in a series of indoor experiments. The results showed that N deposition significantly decreased the growth and survival of this lichen, and the N sensitivity threshold was suggested at 6.0 kg N•haP-1P•yP-1. When the N deposition increased from 8.59 kg N•haP-1P•yP-1 to 14.24, 20.49, 232.99 and 57.99 kg N•haP-1P•yP-1P, the growth rates of lichen thalli decreased by 26.47%, 39.01%, 52.18% and 60.3%, respectively; Whereas the survival rate of the lichen propagules decreased from 92.8% of control(0.0 kg N•haP-1P•yP-1) to 10.7% of 50.0 kg N•haP-1P•yP-1, when they were treated with 0.00, 6.25, 12.5, 25.0 and 50.0Pkg N•haP-1P•yP-1 deposition. Compared with an adequate adsorption of ammonium N, no nitrate adsorption occurred when thalli was submerged in solution lower than 0.4 mM. Our results also suggested that thalli total nitrogen, N:P ratio increased with N availability, and the activity of PME was significantly correlated with thalli total nitrogen. These all indicated that phosphoruous limitation occurred when R. calicaris var. japonica treated with higher nitrogen deposition. Compared with slightly effects of NRA, GSA of R. calicaris var. japonica responded nitrogen availability significantly; In addition, GSA and NRA negatively correlated with thalli growth rate and propagule survival significantly. These results indicated that nitrogen stress do decrease growth and survival of R. calicaris var. japonica, and lichen would be impacted by excess nitrogen in a integrated, not a fragmentary way, including nitrogen uptake, assimilation, even nutrient balance of nitrogen and phosphorous.